2019
DOI: 10.1590/s1678-3921.pab2019.v54.01088
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazolium test for Pinus taeda: preparation, staining, and seed viability classes

Abstract: The objective of this work was to evaluate preparation and staining methods used in the tetrazolium test for Pinus taeda seeds, with the definition of viability classes. The procedures carried out were those described in the rules for seed testing in Brazil and Association of Official Seed Analysts, as well as an alternative method for the tetrazolium test. For each procedure, different combinations of types of seed cuts, concentrations of tetrazolium salt, and exposure periods were used. The test conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The pattern found, which describes the highest percentage of viable seeds in the maximum staining time (3 hours), is due to the fact that it is a batch of viable and vigorous seeds. This result is in accordance with the study presented by (dos Santos et al, 2019) on the viability and vigor of Genipa americana seeds, which showed that increasing the staining time of the seeds produces higher percentages of viable seeds. In our experiment, it was observed that O. pyramidale requires a longer staining time to show high viability, so it would appear that this is the appropriate protocol to analyze the viability of seeds in this species.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The pattern found, which describes the highest percentage of viable seeds in the maximum staining time (3 hours), is due to the fact that it is a batch of viable and vigorous seeds. This result is in accordance with the study presented by (dos Santos et al, 2019) on the viability and vigor of Genipa americana seeds, which showed that increasing the staining time of the seeds produces higher percentages of viable seeds. In our experiment, it was observed that O. pyramidale requires a longer staining time to show high viability, so it would appear that this is the appropriate protocol to analyze the viability of seeds in this species.…”
Section: Discussionsupporting
confidence: 93%
“…In our experiment, it was observed that O. pyramidale requires a longer staining time to show high viability, so it would appear that this is the appropriate protocol to analyze the viability of seeds in this species. dos Santos et al, 2019;Espitia-Camacho et al, 2017;Jácome-Segovia et al, (2019), carried out seed viability studies in forest species to determine the favorable response in terms of concentration and staining time in tetrazolium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, they were classified as viable and non-viable embryos, respectively, observing the following order: Class 1viable and vigorous embryos (Figure 4 ease of identification for viable and non-viable tissues and in its ability to differentiate seed vigor. The colors differences observed in the seeds after staining in tetrazolium solution are the main features to be considered in the interpretation of results of specific tests (Santos, Vieira, & Panobianco, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Some methods are used to determine the physiological quality of seeds of the genus Pinus, such as the spectroscopy-based reserve metabolite profiling analysis (Terskikh et al, 2005), which is still not viable on large scale, and the tetrazolium test, especially for the P. taeda species (ISTA, 2020;Santos et al, 2019). The germination test, however, is the only standard test available to determine the viability of P. taeda seeds (ISTA, 2020).…”
Section: Introductionmentioning
confidence: 99%